The Climatological Features of Atmospheric Rivers and their Role in Water Vapor Transport in the South Polar Region - TAKAHASHI, Kazu; SAKAZAKI, Takatoshi (Journal of the Meteorological Society of Japan. Ser. II, 2025)
In recent years, Atmospheric Rivers (ARs) have been recognized to influence the Antarctic ice sheet via extreme snowfall, latent and sensible heat transports, and anomalous changes in radiation balance. ARs are defined as extreme moisture transport events and are thought to account for a significant fraction of total moisture transport from mid to high-latitude regions, such as Antarctica. While previous studies have investigated ARs associated with extreme events over Antarctica and the Southern Ocean, their climatological features remain poorly understood. We investigate the climatology of ARs in the south polar region such as their geographical distribution and their role in moisture transport, by using an AR detection method that extracts the area with a localized moisture transport at 6-hourly intervals for JRA55. Notably, our method effectively describes the geographical distribution of ARs, contrasting with conventional methods that use temporal fixed criteria. We find that the contours of climatological AR frequency display a zonally asymmetric, spiral-like structure extending from mid-latitudes in the Atlantic to high-latitudes in the Pacific Ocean. This distribution produces a zonal asymmetry in meridional moisture transport, which may contribute to the observed zonally asymmetric distribution of Antarctic precipitation. We also suggest that the dominant meteorological systems associated with the ARs differ geographically: extra-tropical cyclones in the Atlantic and blocking events in the Pacific Oceans. At 60°S, we find that the AR detection number has not had a significant trend over recent decades, but the typical intensity of individual ARs in austral summer has increased over the last 41 years.